Pengaruh Kompetensi (Hard skill) Dan Pelatihan Terhadap Kinerja Pelaksana Teknis Melalui Kepuasan Kerja Sebagai Variabel Intervening (Studi Pada Pelaksana Teknis Dinas PUPR Kabupaten Serang) - Kanafiah, Kanafiah; Prahiawan, Wawan; Suherna, Suherna (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2021)
The purpose of this study is to examine and analyze the elements that influence the performance of technical implementers with the effectiveness of competence (hard skills) and the suitability of training through job satisfaction. This research was conducted at the Department of Public Works and Spatial Planning, Serang Regency, using a descriptive quantitative method using a sample of 120 respondents with an interval scale measurement of 1-10 and analyzed using the Smart PLS 3.29 method. The results of this study state that competence (hard skills) has a significant positive effect on employee performance (technical implementers) with a coefficient value of 10%, training has a significant positive effect on employee performance (technical implementers) with a coefficient value of 22.2%, competence (hard skills) has a significant positive effect. on job satisfaction with a coefficient of 20.6%, training has a significant positive effect on job satisfaction with a coefficient of 44.8% and job satisfaction has a significant positive effect on employee performance (technical implementers) with a coefficient value of 65.5%.